Crystal structure of a new polymorph of bis[μ-1,3-bis(diphenylphosphino)propane-κ2P:P′-disilver(I)] bis(tetrafluoroborate), [Ag(dppp)]2(BF4)2, C54H52Ag2B2F8P4 - Kuang Xiao-Nan; Lin Sen; Li Si-Fan; Li Yue; Xin Xiu-Lan; Jin Qiong-Hua (Zeitschrift für Kristallographie - New Crystal Structures, 2018)
C54H52Ag2B2F8P4, triclinic, P1̄ a = 11.4869(4) Å, b = 12.9118(5) Å, c = 19.6858(6) Å, α = 100.8240(10)°, β = 102.185(2)°, γ = 110.470(3)°, V = 2562.31(15) Å3, Z = 2, Rgt(F) = 0.0263, wRref(F2) = 0.0666, T = 293(2) K.